11-β hydroxysteroid type 1 knockout mice display an antidepressant-like phenotype in the forced swim test. Issue 1 (24th September 2015) - Slattery, David A.; Uzunov, Doncho P.; Cryan, John F.
Abstract : Objective: 11β-dehydroxysteroid dehydrogenase (HSD) types 1 and 2, enzymes are involved in the activation and inactivation of glucocorticoids in vivo, respectively. Indirect evidence implicates two enzymes in the aetiology of depression but no study has directly assessed the potential role of 11 β-HSD1 in animal tests. Methods: We assessed 11 β-HSD1 knockout mice in the forced swim test (FST), tail suspension test (TST) and for locomotor activity. Results: Genetic ablation of the 11β-HSD1 gene results in an antidepressant-like phenotype in the FST; the most widely utilised animal test of antidepressant activity, but not in the related TST. This may be related to the different biological substrates underlying these tests. The decreased FST immobility was not due to alterations in general activity. Conclusions: Taken together these results suggest that 11β-HSD1 may play an important role in depression-related behaviours and further studies are necessary to fully characterise its role in such behaviour.